PEMANFAATAN MEDIA DIGITAL UNTUK MENDUKUNG LITERASI MEMBACA MASYARAKAT KOTA SERANG - Sutoro, Moh.; Ma'arif, Minhatul; Fatari, Fatari; Khaeruman, Khaeruman; Maharani, Aditya (Yayasan Education and Social Center, 2025)
This community service program aimed to improve participants’ digital literacy, reading frequency, reading motivation, and comprehension of digital texts. The program was implemented over two weeks in September across various community locations, including community halls, health posts, elementary schools, and mobile reading corners. The method employed a participatory, community-based approach using interactive digital media such as e-books, audiobooks, and online library platforms. Results showed significant improvements in digital literacy, reading frequency, motivation, and comprehension among participants. The program enhanced not only technical reading skills but also literacy awareness and sustainable reading habits. The implications include community empowerment through digital literacy and strengthened critical information filtering skills. It is recommended that the program continue with further mentoring and the development of age-appropriate modules. This initiative is expected to serve as a model for digital literacy development in other communities.